An Empirical Model for Information Retrieval System Evaluation: The User's perspective - Akhigbe, Bernard Ijesunor; Afolabi, Babajide; Adagunodo, Emmanuel Rotimi (Computer Engineering and Intelligent Systems, 2023)
Vol 2, 2011 .Pages 34-45